KEKERASAN DI ORGANISASI INTRA KAMPUS PARADOKS PENDIDIKAN KRITIS STUDI KASUS: KEKERASAN PADA MAHASISWA PENCINTA ALAM (WAPEALA) UNIVERSITAS DIPONEGORO - Heharero Tesar Ashidiq; Fitriyah . (Journal of Politic and Government Studies, 2019)
This research is based on the event of violence acts that have been occurring long enough and continuously. The phenomenon where some students died while taking part in the students of nature lovers basic education process had several errors of education method.The purpose of this study is to analyze the violence that occurs in intra-campus organizations, especially Nature Lovers Students (Wapeala) Diponegoro University through a critical education perspective. The research method used is a qualitative method with an ethnographic and phenomenological approach. Data collection techniques used were participant observation and presented descriptively.Violence in the education process was inseparable from power by the ruling class. By using the authority and power possessed, there is a irrelevancy from the basic purpose of education. The results of this study indicate that education process at wapeala still has several physical violence, verbal violence, symbolic violence and neglect. Furthermore, there is a phase that dialogue between seniors and juniors had disappear, that’s why the opportunity to abuse power is greater than before.Violence in education can be said as a paradox of the education’s purpose. Violence is used as a tool to maintain capability as a Wapeala’s senior in carrying out the education process. From the victim's perspective, the consequences of using violence have more impact than the purpose of using violence itself.Key Words : Violence, power, critical education.